Kilka uwag o imionach rodopskich Pomaków - Walczak-Mikołajczakowa, Mariola (Poznańskie Spotkania Językoznawcze, 2014)
Pomacs are Bulgarian speaking Muslims who accepted Islam between 15th and 19th century. Most of contemporary population of Pomacs, counting overall about 400 thousands, live in the Rodops (the part of the Greek side). For many years the assimilation attempt has been making on this population by changing their Muslim names and surnames. This article concerns about the reasons and the prizes which are paid for these changes. Author relies on her own research and confronts own remarks with dictionary data.